SOCIAL SECURITY AS AN INSTRUMENT TO PROTECT VICTIMS. OF DOMESTIC VIOLENCE IN BRAZIL (CIPEEX, 2025)
This paper aims to analyze how social security rights can be implemented as an effective mechanism for protection and financial support for victims of domestic violence, considering the existing regulatory gaps and the challenges in implementing public policies aimed at this vulnerable group. Domestic violence is a violation of human rights and is fundamentally linked to gender inequalities, becoming a persistent reality throughout the world, especially in Brazil. Thus, this study will seek to discuss the history of domestic violence in Brazil and the evolution of the Maria da Penha Law, as well as the different types of domestic violence provided for in the law and their rates, in addition to examining social security as an instrument for protecting victims, focusing on sickness benefits and survivor's pensions in cases of violence.
Keywords: Domestic violence; Women's rights; Social security